Extending the concept of familiness to relational capability: A Belgian micro-brewery study. (March 2018) - McGrath, Helen; O'Toole, Thomas
While research in family businesses has focused on familiness as a resource with potential to generate competitive advantage, a gap exists in understanding how such value can be extended to wider business relationships. We contribute to an increased understanding of how familiness can influence the development of relational capability in entrepreneurial family firms. Using a business relational and family embedded perspective, we advance a conceptualisation of the link between familiness and relational capability based on an analysis of the extant literature and qualitative case research. The critical role of the family identity emerges through the empirical study. As such, we find six relational processes across family identity which link or mitigate the movement between familiness and relational capability. Theoretical and practical implications are offered.